Abbreviated multi‐breath washout for calculation of lung clearance index1. Issue 4 (25th July 2012) - Robinson, Paul D.; Stocks, Janet; Aurora, Paul; Lum, Sooky
Abstract Introduction Various functional residual capacity (FRC) repeatability criteria have been proposed for lung clearance index (LCI) measurement by multiple breath washout (MBW). Adult guidelines recommend three technically acceptable tests with FRC values within 10%, whilst preschool guidelines recommend two such tests. Feasibility of and need for recommendations in children is unclear. Methods Retrospective analysis of MBW data was undertaken in healthy control (n = 90) and cystic fibrosis (CF) subjects (n = 108) encompassing infancy, pre‐school and school age ranges. Feasibility of FRC repeatability recommendations was investigated in those with three technically acceptable tests. Validity of mean LCI from the first two tests alone (vs. all three) was investigated by comparing mean data and sensitivity to detect abnormal peripheral airway function in CF. Results LCI coefficient of variation (CoV) was related to FRC CoV (P < 0.001) and disease category (P = 0.002). Application of adult repeatability criteria decreased LCI CoV (4.7 vs. 8.5%, P < 0.001), but had poor feasibility beyond infancy (62/150, 41%). Preschool recommendations increased feasibility but only to 70% overall. There was no difference in mean LCI (All three minus 1st two tests) in healthy controls [mean (95% CI) difference: 0.02 (−0.01, 0.06; P = 0.15)], this difference being statistically but not clinically significant in CF subjects [0.07 (0.00, 0.13; P = 0.04)]. Sensitivity in CF subjects was unaffected. Conclusion Adult FRC repeatability recommendations improved LCI repeatability in pediatric subjects, but poor feasibility limited utility. In an experienced pediatric MBW center, recent preschool recommendations can be extended to two technically acceptable tests, irrespective of FRC repeatability, without significantly affecting mean LCI or compromising sensitivity. Pediatr Pulmonol. 2013; 48:336–343. © 2012 Wiley Periodicals, Inc.